Da administração ao marketing digital: um estudo taxonômico-terminográfico bilíngue baseado em corpus - Mateus, Lucas Amâncio (2022)
The product-market relations which permeate the practices of Management, Marketing, and Digital Marketing have expanded in recent years, creating the need for scientific and terminographic studies about these fields of knowledge. Using the theoretical foundations of Terminology and Terminography (BARROS, 2004; KRIEGER; FINATTO, 2004) and of Corpus Linguistics (BERBER SARDINHA, 2004; TEIXEIRA, 2008; TOGNINI-BONELLI, 2001), we focus on building a proposal for a bilingual and bidirectional vocabulary (Portuguese/English) for Digital Marketing, aiming to meet the needs of students of business courses and Translation professionals. The vocabulary is published in the Terminology management web environment called VoTec (FROMM, 2007, 2022), available for free access at: http://pos.votec.ileel.ufu.br. Our specific objectives were: (i) to demonstrate the method of construction of concept maps for the fields of Management, Marketing and Digital Marketing; (ii) to establish a proposed definition model for Digital Marketing terms, and (iii) to make the entries and their definitions available on VoTec. The theoretical and methodological framework, based on the Communicative Theory of Terminology (CABRÉ, 1993, 1999), on the concepts of vocabulary (BARBOSA, 1992) and definitional contexts (AUBERT, 2001), and on the intersections between Corpus Linguistics, Translation, Phraseology, and Information Science (CARLAN, 2010), provided the basis for building the domain trees and for creating the Digital Marketing vocabulary. After building the concept maps, we proceeded to the compilation of corpora and the identification of term candidates. For the analyses, we used the WordSmith Tools 7.0 program (SCOTT, 2016). The results obtained showed that the taxonomy of the business area present in the scientific means is outdated or missing. Thus, a taxonomy could be built based on specific criteria of frequency and relevance of the sources, along with the use of componential analysis (ILARI, 2002). The subcorpora of study, in Portuguese and English, are composed of texts of the scientific-academic and instructional genres (blogs). We arrived at the definition of 16 terms that compose the proposed vocabulary, which are the names of the Digital Marketing sub-branches, plus the names of this branch of study. The microstructure of the vocabulary follows the VoTec paradigms, and the definitions are contrastive and based on the definitional contexts analyzed from the subcorpora of study.